1976
DOI: 10.2136/sssaj1976.03615995004000010017x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Selenite and Phosphate on an Allophane Clay

Abstract: Selenite was adsorbed on an allophane clay from solutions of different concentrations at pH 5.0, at 30C, and under a N2 atmosphere, and the amounts of sulfate, silicate and hydroxyl ions released were measured. The results were compared with those from a similar study with phosphate on the same clay.The results indicate that at low concentrations both phosphate and selenite exchanged with adsorbed sulfate, adsorbed silicate, and aquo and hydroxo groups. About three times more phosphate than selenite was adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 0 publications
6
33
0
Order By: Relevance
“…The release of OHaccompanied with Se(IV) sorption on allophane clay was larger than that by P(V) sorption (Rajan and Watkinson 1976). Although most researchers have concluded that the increase in the solution pH with a certain anion adsorption on particles indicates the release of OH -from the particle surface, our results are based on the reaction (5) described by Zhang and Sparks (1990).…”
Section: (V) [ As(v)=se(iv) [ Silicate (Si(iv)) [ Mo(vi) [ Sulfate (Smentioning
confidence: 57%
“…The release of OHaccompanied with Se(IV) sorption on allophane clay was larger than that by P(V) sorption (Rajan and Watkinson 1976). Although most researchers have concluded that the increase in the solution pH with a certain anion adsorption on particles indicates the release of OH -from the particle surface, our results are based on the reaction (5) described by Zhang and Sparks (1990).…”
Section: (V) [ As(v)=se(iv) [ Silicate (Si(iv)) [ Mo(vi) [ Sulfate (Smentioning
confidence: 57%
“…This fern can be categorized as a Se-accumulator, according to the standards suggested by Baker (1981). Simultaneously, the higher Se accumulation for Chinese brake fern in nutrient solution culture than that in soil culture indicate that selenite might probably be adsorbed in soils (Rajan and Watkinson 1976). The adsorption of Se in soils may significantly retard the uptake of Se by Chinese brake fern.…”
Section: Discussionmentioning
confidence: 99%
“…The sorption of selenite onto mineral and oxide surfaces has been very extensively studied (e.g. Hingston et al 1974;Rājan and Watkinson 1976;Parfitt 1978;Rajan 1979;Balistrieri and Chao 1987;Saha et al 2004) and thought to explain the poor bioavailability of Se in soil. Overall, studies on the behaviour of Se in soil have emphasized the inorganic chemistry of Se.…”
Section: Discussionmentioning
confidence: 99%